Arquitetura no nordeste brasileiro e o roteiro de Armando Holanda - Woensel, Fernando Coutinho Van (2016)
This study aimed to investigate the correspondence of the principles in Armando Holanda´s book Roteiro para construir no Nordeste in architectural projects produced in northeastern Brazil from 1976 (its publishing year) to 1985. This research chose to use the Projeto magazine as its documentary source for the selection of these works, which is one of the main architecture periodicals in Brazil, making use of the LPPM's / PPGAU / UFPB collection. The initial list of seventy projects was submitted to selection criteria, resulting in a collection of 29 projects – five of them were considered representative and were more deeply analyzed. The research found, among other conclusions, that from the nine principles proposed by Holanda in his book, 60% of them were found in such projects.